2006
DOI: 10.1089/ham.2006.7.193
|View full text |Cite
|
Sign up to set email alerts
|

High Altitude Adaptation in Tibetans

Abstract: Since the beginning of the Himalayan climbing era, the anecdotal extraordinary physical performance at high altitude of Sherpas and Tibetans has intrigued scientists interested in altitude adaptation. These ethnic groups may have been living at high altitude for longer than any other population, and the hypothesis of a possible evolutionary genetic adaptation to altitude makes sense. Reviewed here is the evidence as to whether Tibetans are indeed better adapted for life and work at high altitude as compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
181
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 203 publications
(193 citation statements)
references
References 86 publications
7
181
0
1
Order By: Relevance
“…Tibetans show greater adaptability to the hypoxic environment of high-altitude regions compared to people belonging to the Han ethnicity; the incidence of HAPE was significantly less in Tibetans compared to that observed in people belonging the Han ethnicity (Cheng et al, 1997;Basu et al, 2007). Genetic factors accounted for approximately 50% of the factors influencing the adaptation of the human body to highaltitude hypoxic environments (Wu et al, 2005;Wu and Kayser, 2006). In this study, 10 susceptibility genes related to HAPE were identified/screened from the NCBI database; these genes coded for aldosterone synthase 2 (CYP11B2), ACE, heat-shock protein-70 (HSP70), nuclear factor-kappa B (NF-κB), SP-A2, NOS,VEGF,prolyl hydroxylase (EGLN1), and the zinc finger protein A20.…”
Section: Discussionmentioning
confidence: 99%
“…Tibetans show greater adaptability to the hypoxic environment of high-altitude regions compared to people belonging to the Han ethnicity; the incidence of HAPE was significantly less in Tibetans compared to that observed in people belonging the Han ethnicity (Cheng et al, 1997;Basu et al, 2007). Genetic factors accounted for approximately 50% of the factors influencing the adaptation of the human body to highaltitude hypoxic environments (Wu et al, 2005;Wu and Kayser, 2006). In this study, 10 susceptibility genes related to HAPE were identified/screened from the NCBI database; these genes coded for aldosterone synthase 2 (CYP11B2), ACE, heat-shock protein-70 (HSP70), nuclear factor-kappa B (NF-κB), SP-A2, NOS,VEGF,prolyl hydroxylase (EGLN1), and the zinc finger protein A20.…”
Section: Discussionmentioning
confidence: 99%
“…Populations at high altitude could therefore benefit from enhancing the facilitatory mechanisms or suppressing the inhibitory ones. Some highland species or populations are characterized by a heightened acute hypoxic ventilatory response, a more effective breathing pattern, a maintained acclimatization response, and/or a prevention of hypoxic desensitization (Black and Tenney, 1980;Beall et al, 1997;Wu and Kayser, 2006;Brutsaert, 2007;Scott and Milsom, 2007;Pichon et al, 2009). The underlying chemoreceptive mechanisms are not necessarily convergent at the cellular level.…”
Section: The Nature Of Physiological Adaptation To High-altitude Hypoxiamentioning
confidence: 99%
“…However, pulmonary O 2 diffusion capacity can be enhanced further in some high-altitude adapted groups that have larger lungs than lowlanders (Brutsaert et al, 1999;Wu and Kayser, 2006;Brutsaert, 2007;Scott et al, 2010). This is particularly true in birds because their lungs are rigid and are ventilated by air sacs.…”
Section: The Nature Of Physiological Adaptation To High-altitude Hypoxiamentioning
confidence: 99%
“…The rs2294008 CT and TT genotypes were similar in the Tibet (39.51%, 6.64, respectively) and Han (40.86%, 7.14, respectively) populations, but were significantly lower than those of the Hui population (46.03%, 13.02, respectively). The Han nationality constitutes the majority population, while Tibetans are a minority in the Qinghai area in China, with both groups having resided in a high-altitude area for a long period of time, thus their physical and physiological functions have altered to adapt to hypoxic environments (38). A recent study has identified that advantageous gene variations are associated with human adaptation at high altitudes (39), thus, genetic susceptibility of the Tibet and Han populations may yield different results from Han populations only.…”
Section: Intestinal Cases Diffuse Cases -----------------------------mentioning
confidence: 99%